Inovasi Model Pengembangan Pendanaan Koperasi Melalui Penerbitan Sukuk: Analisis Komprehensif pada Koperasi Peternak X - sugiyanto, Sugiyanto; Wandani, Syahrudin; Indriyani, Yuanita (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Cooperatives in developing countries, including Indonesia, face structural challenges in accessing long-term funding sources. Dependence on internal funding and cultural resistance to the interest-based system of conventional banking complicate business expansion efforts. This study aims to analyze and develop an innovative funding model for cooperatives through the issuance of Sukuk, with a comprehensive case study on the Livestock Farmers Cooperative X. The research method uses a qualitative approach with an intrinsic case study design, where data was collected through in-depth interviews, participant observation, and document studies. The results reveal that members' investment interest is strongly influenced by behavioral factors (such as trust in the management) and religious factors (sharia compliance), in addition to economic factors. To address the regulatory gap, a hybrid legal construction and a collective scheme were designed, enabling the cooperative to meet capital market requirements without sacrificing the principle of open membership. The proposed Sukuk structure is a Mudharabah Sukuk with a revenue-sharing mechanism, equipped with an investor protection mechanism and a structured sinking fund. This model represents a harmonious integration of Islamic finance principles, cooperative values, and behavioral finance theory, thereby offering a feasible, strategic, and contextual funding solution for cooperatives. Keywords: Innovative Model of Cooperative Financing, Sukuk, Islamic Finance, Behavioral Finance, and  Mudharabah